Different dominating mass transport mechanisms for drying and sorption of toluene-PMMA films – Visualized with Raman spectroscopy. (22nd April 2021) - Merklein, Lisa; Eser, Jochen C.; Börnhorst, Tobias; Könnecke, Niklas; Scharfer, Philip; Schabel, Wilhelm
Abstract: The phase equilibrium as well as the diffusion kinetics of toluene-poly (methyl methacrylate) have been investigated over a concentration range from 0 to 75 v% toluene with independent measurements in order to describe drying and sorption processes under different conditions. The phase equilibrium of a micrometer thick layer, measured using a magnetic suspension balance can be confirmed with quartz crystal microbalance measurements of layers in the nanometer range. The diffusion kinetics has been determined to be concentration- and temperature-dependent using experimental data from drying experiments gained via inverse micro Raman-spectroscopy. A different mass transport behavior can be observed for sorption experiments. The determined mass transport behavior of both, drying and sorption measurements can be verified by experiments with a magnetic suspension balance. In total, the determined data permits the modeling of an integral drying process under different drying conditions as well as the prediction of concentration profiles in the film. Graphical abstract: Image 1 Highlights: Experimental data regarding the thermodynamic behavior of the system PMMA-toluene. Raman spectroscopy measurements investigating sorption and desorption kinetics. Crosschecking the generated data with different techniques. Comparison of simulation and experiment for drying of toluene from PMMA.